Capital Mobility and the Output-Inflation Tradeoff - Razin, Assaf (IMF Working Papers; Working Paper, 2000)
Identifying determinants of the output-inflation tradeoff has long been a key issue in business cycle research. We provide evidence that in countries with greater restrictions on capital mobility, a given reduction in the inflation rate is associated with a smaller loss in output. This result is shown to be consistent with theoretical presumption from a version of the Mundell-Fleming model. Restrictions on capital mobility are measured using the IMF's Annual Report on Exchange Rate Arrangements and Exchange Restrictions. Estimates of the output-inflation tradeoff are taken from previous studies, viz., Lucas (1973) and Ball, Mankiw and Romer (1988).